The role of parents and teachers in developing students' problem-solving creativity through scout activity - Khulatul Lutfiah; Sri Marwiyati; Hesti Ariestina (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2020)
This research aims to know parents' and teachers' role in developing problem-solving creativity by Scouting Activity in MIN Salatiga and MI Ma'arif Mangunsari. Besides that, it is to see the form of program to create the problem-solving creativity in the Scouting Activity in these Islamic School.This research is qualitative research, which results from the descriptive data. The technique of collecting the data include interview, documentation, and questionnaire. The data was analyzed using the Data Reduction Method, Data Presentation, and the Data Validity Test using triangulation.This research shows that: 1) Both MIN Salatiga and MI Ma'arif Mangunsari give immense support in developing problem-solving creativity. 2) The development of problem-solving creativity in the Scouting Activity in MIN Salatiga and MI Ma'arif Mangunsari principled on mastering five primary Scouting skills containing Spiritual, Emotional, Social Skill, Managerial Skill, and Physical Skill. From several techniques and material given by the Scouting, guidance can make the students capable of seeking problem-solving, which can be applied to themselves and the society around them.